Research on Containment Passive Heat Sink System - SHENG Meiling;ZHANG Xin;LIANG Xiao;QIU Jinmeng (Yuanzineng kexue jishu, 2023)
The Gen Ⅲ nuclear power plant HPR1000 possesses domestic independent intellectual property rights. Aiming at the continuous optimization, improvement and innovation research of HPR1000, a new containment passive heat sink system which can transfer the containment heat under design basis accident conditions was proposed based on the existing passive containment cooling system configuration of HPR1000. This new system used ice with a large heat capacity as the passive heat sink. Based on the existing reactor building layout of HPR1000, the ice capacity was analyzed, the water chilling unit performance was calculated by heat balance calculation, and then the safety function capacity in response to design basis accident of the containment passive heat sink system was demonstrated. The temperature and pressure response of the containment under large LOCA conditions were simulated and analyzed in the following four cases: 1) case 1, the current configuration scheme of HPR1000 containment, the passive containment cooling system was not started; 2) case 2, the current configuration scheme of HPR1000 containment, the passive containment cooling system was started; 3) case 3, the containment passive heat sink system was configured, and the passive containment cooling system was not started; 4) case 4, the containment passive heat sink system was configured, and the passive containment cooling system was started. The results of case 1 and case 3 show that when the passive containment cooling system is not started, the containment would be eventual failure because of the containment heat cannot be smoothly exported to the outside of the containment. The current configuration scheme of HPR1000 fails to activate the passive containment cooling system at 14.85 h after the accident. After adopting the containment passive heat sink system, the containment pressure reaches 0.276 MPa (absolute pressure) 24 h after the accident, exceeding the limit requirement that the containment pressure after 24 h under the design basis condition should be less than half of the design pressure (i.e. 0.26 MPa (absolute pressure)), and the containment is damaged about 41.85 h after the accident. The comparison of case 1 and 3 shows that if the passive containment cooling system is not configured or started, the containment passive heat sink system can only delay the time of containment failure and cannot reduce the risk of containment overpressure. The results of case 2 show that, under the condition that the passive containment cooling system is activated, the containment pressure reaches 0.51 MPa (absolute pressure) 24 h after the accident, and the peak containment pressure reaches 0.519 8 MPa (absolute pressure) about 31.6 h after the accident, although it does not exceed the design pressure of the containment. However, it cannot meet the limit requirements for the design basis condition. The results of case 4 show that, through reasonable ice room design, the temperature and pressure of the containment can be controlled at a low level under the design basis condition. The containment pressure rises slowly from 0-75 h after the accident and reaches 0-194 MPa (absolute pressure) 24 h after the accident. With the continuous melting of the ice and continuous thermal conductivity of the passive containment cooling system, the peak pressure of 0.259 MPa (absolute pressure) reachs about 40.9 h after the accident, which is still less than half of the design pressure of the containment. Subsequently, with the continuous operation of the passive containment cooling system, the containment pressure slowly decreases, ensuring the integrity of the containment, while maintaining the internal temperature of about 110 ℃. The results of all cases show that the passive containment cooling system equipped with a certain ice capacity can control the temperature and pressure of the containment within the safety limit within 24 h to ensure the integrity of the containment. The containment passive heat sink system is independent of the power supply, the process system is simple, and the heat absorption effect is significant. It can effectively improve the ability of HPR1000 to deal with the design basis accident, further simplify the existing configuration of HPR1000, and improve the economy.